Renal swelling indicates renal damage in infants with their first urinary tract infection. (25th July 2018) - Simrén, Y; Valdimarsson, S; Stokland, E; Lagerstrand, K M; Sixt, R; Hansson, S
Abstract: Aim: We used ultrasound to evaluate renal swelling as a predictor of acute and permanent renal damage in infants with their first urinary tract infection (UTI). Methods: The cohort at the Queen Silvia Children's Hospital, Gothenburg, Sweden, comprised 101 infants with their first UTI at a mean age of 3.9 ± 3.0 months. Acute and follow‐up ultrasounds were carried out a few days and one month after treatment started, and a 99m technetium dimercaptosuccinic acid (DMSA) scan was carried out after one month and after a year if the first scan was abnormal. Results: The acute ultrasounds showed that renal length and volume, calculated as standard deviation scores (SDS), were 1.39 ± 1.43 SDS and 1.30 ± 1.08 SDS. We found that 52% of the one‐month DMSA scans and 25% of the one‐year DMSA scans were abnormal. Renal length (p = 0.0026) and initial volume (p = 0.0005) on the ultrasound predicted acute renal damage at the one‐month DMSA scan and initial renal length (p = 0.030) predicted permanent renal damage at the one‐year DMSA scan. Conclusion: Renal swelling was associated with renal damage. Although the diagnostic performance compared with the DMSA scan was weak, renal swelling may help clinicians to make decisions about further investigations and follow‐ups of infants with UTIs.